Comparison of bond strength between self-adhered and conventional composites - Putra, Adria Permana; Karlina, Elin; Febrida, Renny (Padjadjaran Journal of Dentistry, 2010)
Bond strength towards dentine is a critical factor for composite restoration success. The purpose of this research was to obtain data on self-adhered composite bond strength to tooth dentine. This research was an experimental laboratory research that used 10 third molar teeth as samples. The teeth were prepared by thinning its mesial part until it reaches dentine layer. The sample was divided into two groups, each consisting of 5 teeth. In group I was applied self-adhered composite with Fusio® Liquid Dentine brand, whereas group II was applied conventional composite with Ivoclar Te-Econom Flow®. The applied composite had a cylindrical shape with 6 mm diameter. The sample was then placed on the test arm. The shear bond strength test method then conducted on Universal Testing Machine (UTM). Obtained data was tested using Two-tails Independent t-Test (α = 0,05). The results showed the average of self-adhered composite bond strength to dentine is 1,8878 ± 0,2859 MPa and conventional composite for 4,43552 ± 0,49472 MPa. The data showed that the self-adhered composite bond strength to dentine is smaller than conventional composite. From this research can be concluded that there was bond strength difference between the self-adhered composite with conventional composites towards the tooth dentine.